Edukasi Gizi Seimbang melalui Media Game Nutristzil Berbasis Interactive Website di SMK Mahardhika Batujajar - Salsabila, Nanda Fitria; Putri, Viola Syarwendah; Ramadhan, Miftahul Akbar; Nugraheni, Dian; Anshori, M. Wildan; Astuti, Widya (Jurnal SOLMA, 2024)
Background: The lack of knowledge regarding balanced nutrition intake in adolescents resulted in suboptimal diets. Therefore, there is a need for an educational program aimed at transforming their diet following balanced nutrition guidelines. Method: The partner of this activity is class 10 RPL 2 at SMK Mahardhika Batujajar, the number of participants is 35 people, providing education on balanced nutrition through Nutristzil, an interactive web-based game. The effectiveness of this program was evaluated through pretest and posttest results. In addition, the program also includes training in website and game development, with the expectation that teachers and students studying software engineering can develop resources for nutrition education and other topics after the program’s completion. Result: The evaluation results reveal a significant difference in knowledge before and after the program, indicating a positive response from the students. Conclusion: Behavioral change can be achieved through the establishment of new habits practiced consistently for 21 days.